Acute effect of basketball-specific exercise on lower limb injury risk mechanisms in male basketball players u16 and u18 - Lehnert, M.; Hùlka, K.; De Ste Croix, M.; Horutová, K. (Research & Investigations in Sports Medicine, 2018)
The aim of this study was to examine and compare the acute effects of basketball-specific fatigue on muscular stiffness and reactive strength in male adolescent basketball players of two age categories. Reactive strength, expressed by means of the reactive strength index (RSI), and leg stiffness (LS) as mechanisms associated with the risk of ACL injury were measured in eleven players of the U16 category (age 16.1±0.4 years; body height 185±6.5cm; body mass 74.3±9.9kg) and ten players of the U18 category (age 17.7±0.4 years; body height 187±5.7cm; body mass 79.7±7.4kg) pre and post simulated basketball match play (SBFP28). RSI was determined by a drop jump test, LS by a 20 sub-maximal two-legged hopping test. No significant effects of SBFP28 on the monitored parameters were observed with the exception of RSI in U16 (p=0.013, r=0.53). Similarly, there were no significant differences in the fatigue-related responses to SBFP28 for RSI and LS between the age groups. These results indicated that irrespective of age, the stabilization function of the knee muscles was not impaired and consequently the risk of ACL injury was not increased.